Enhancing the Conceptual, Procedural and Flexible Procedural Knowledge of Pre-Service Mathematics Teachers in Algebra - Otun, Wasiu Ismaila; Olaoye, Adetunji Abiola (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
The study investigated the effects of Solve-Reflect-Pose Strategy (SRP) on pre-service mathematics teachers’ algebraic knowledge for teaching in Nigeria. A pre-test-post-test quasi experimental design was employed. Intact classes were used and in all, 182 pre-service mathematics teachers’ participated in the study (92 in the experimental group taught with the SRP and 90 in the control group taught using the Modified Conventional Method (MCM). One research instrument manipulated at three levels namely: Conceptual Knowledge Test (CKT), Procedural Knowledge Test (PKT) and Flexible Procedural Knowledge Test (FPKT), was used for the quantitative data and interview protocol for qualitative data. The two research questions formulated were analysed using descriptive statistics while independent sample t-test was used to analyse the two hypotheses. Results showed that there were statistically significant differences in the mean post-test achievement scores on conceptual knowledge test, procedural knowledge test and flexible procedural knowledge test between pre-service teachers exposed to the SRP and those exposed to the MCM, all in favour of the SRP group. Based on the results, SRP should be adopted as an instructional strategy and efforts should be made to integrate the philosophy of SRP into the pre-service teachers’ curriculum at the teacher-preparation institutions.